Perencanaan Dinding Core Wall Pada Gedung Bertingkat Tinggi - Irma Wirantina Kustanrika (Sekolah Tinggi Teknik - PLN, 2016)
In buildings , the electoral structure of the core wall are concerned, of the type of core wall core wall is open or closed wall cores , material , shape and others . Because a stiffener in high-rise buildings are also basically behaves as the core of the building whose function is to eliminate lateral forces such as seismic forces , the forces of wind and others . Required core strong wall that can withstand lateral loads that exist . Selection of the type of core wall efficiently to cost, quality and time for a multi-storey building can be done by determining the type of material used and also form the core wallnya . It is based also on the shape of the building to be made as well as the function of the building later.